Seroprevalence of Hepatitis B and Hepatitis C in end-stage renal disease patients on maintenance hemodialysis: a single-center study from Bangladesh - Sarwar, S. M. Rahid; Rahman, A. K. M Mijanur; Rahman, S. M. Mijanur; Selim, Shahjada; Hasan, A. B. M. Kamrul (International Journal of Advances in Medicine, 2019)
Background: Hepatitis B virus (HBV) and Hepatitis C virus (HCV) infections are important causes of morbidity and mortality in hemodialysis (HD) patients. The aim of this study was to estimate the seroprevalence of HBV and HCV among end-stage renal disease (ESRD) patients on maintenance HD. Methods: This cross-sectional study was conducted in the hemodialysis unit of a military hospital of Bangladesh from October 2013 to March 2014 and included 141 maintenance HD patients. All patients were assessed by HBsAg and anti-HCV antibodies in addition to routine liver function tests. Results: The age range of the study subjects were 18-70 years, and the majority (85.11%) were male. Among them 22 (15.60%) were positive for anti HCV, 5(3.5%) were positive for HBsAg, and 3 patients (2.13%) were positive for both HBsAg and anti-HCV. The duration of hemodialysis was higher in anti-HCV positive patients (49±24 vs. 25±10 months, p <0.05) than anti-HCV negative ones. Anti-HCV positive patients in this study received a higher number of blood transfusion (units) than anti-HCV negative patients (7.5±4.3 vs. 2.8±1.7 units, p <0.05). HBsAg positive patients also received a higher number of blood transfusion (units) than HBsAg negative patients (8.2±3.1 vs. 3.2±1.2 units, p <0.05). Conclusions: Hepatitis C virus was the major form of hepatitis in HD patients in this study. The duration of HD was higher in anti-HCV positive patients; the numbers of blood transfusion units were higher in patients positive for HCV and HBV than the negative ones.